Comparing the outcomes of traumatic cervical spinal cord injuries in patients presenting with fracture-dislocation versus those with cervical canal stenosis - Morteza Taheri; Abdolhadi Daneshi; Mohammad Hossein Ghazvini; Parisa Javadnia (Interdisciplinary Neurosurgery)
Aim: In this research, we evaluated the long-term outcomes of patients who experienced traumatic cervical spinal cord injuries resulting from fracture-dislocation or canal stenosis. Methods: Seventy-two patients with traumatic cervical spinal cord injuries, aged 18 to 72 months post-injury, were evaluated. Participants were categorized based on the etiological mechanism of injury, specifically canal stenosis versus fracture-dislocation. Comparative analyses were conducted between these two groups to assess differences and outcomes. Results: The mean age of patients was 44.47 ± 15.32 years, with a male predominance at 81.9 %. Among the patients, 43 experienced cervical cord injuries attributed to fracture-dislocations of the cervical vertebrae, while 29 had injuries resulting from cervical canal stenosis. The predominant mechanism of trauma was falls, followed by motor vehicle accidents. The C5 vertebra was the most frequently fractured level, with C5/C6 and C6/C7 noted as the most common dislocation levels. The mean interval from injury to surgical decompression was 4.27 ± 6.98 days, with an average hospitalization duration of 22.83 ± 21.76 days. The mean follow-up period was 43.83 ± 14.43 months. Statistical analysis revealed significant differences between the two groups concerning age, hospitalization duration, trauma mechanism, clinical presentation, incomplete cord injury status, and in-hospital mortality. However, the outcomes—including post-discharge mortality and scores on SF12 PCS and SF12 MCS—showed no significant differences between the groups. Conclusion: This study demonstrated that, while short-term outcomes, particularly in-hospital mortality, are elevated in patients presenting with fracture dislocation compared to those with cervical canal stenosis, long-term prognoses do not inherently indicate worse outcomes in terms of mortality or quality of life for the former group.